Appalachia / America - Somerville, Wilson (Appalachian State University, 1981)
This volume of the Proceedings of the 3rd Annual Appalachian Studies Conference, held in 1981, offers a collection of some of the more important papers presented at the conference. Paper topics include labor and the economy; land in Appalachia; urban Appalachia; education; and values and culture.